Under graduate student feedback on teaching and evaluation method in clinical pharmacology - Deo, SK (Journal of College of Medical Sciences-Nepal, 2014)
Background Any teaching and evaluation method can be considered as effective once they are judged by students. Objective This study was designed to obtain feedback on teaching and evaluation methods in the subject of clinical pharmacology among under graduate students Methods Feedback on teaching and evaluation method was taken from undergraduate students of 2009 batch and various approaches to teaching and evaluation are identified. To know the effect of these novel approaches of teaching and evaluation, student feedback was taken from subsequent batch 2010 and 2011 using a written validated questionnaire covering various aspects of teaching and evaluation methods. Results Under graduate students were satisfied with all teaching methods like lecture and pharmacological exercises. They showed preference for tutorials, short answer questions and revision classes where as they were not satisfied with seminar method of learning. All students felt that there should be more time for clinical pharmacology and pharmacological problem based exercises.. The pass percentage of the subsequent batch in university examinations improved from 75 % to 90%. Conclusion Based upon the student’s feedback, incorporation of suggestion obtained from the students resulted in improvement in performance of the students. Hence, it is very essential to take regular feedback from the students to synchronize teaching and evaluation method of the students. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 31-34